Synthesis, structure and cytotoxicity of cyclic (alkyl)(amino) carbene and acyclic carbene complexes of group 11 metals. Issue 45 (8th November 2017) - Bertrand, Benoît; Romanov, Alexander S.; Brooks, Mark; Davis, Josh; Schmidt, Claudia; Ott, Ingo; O'Connell, Maria; Bochmann, Manfred
Abstract : Synthesis of group 11 metal CAAC and acyclic carbene complexes with low micromolar cytotoxicity towards human cancer cells. Abstract : A series of complexes of cyclic (alkyl)(amino)carbene (CAAC) complexes of copper, silver and gold have been investigated for their antiproliferative properties. A second series of acyclic carbene (ACC) complexes of gold(i ) were prepared by nucleophilic attack on isocyanide complexes by amines and amino esters, to give (ACC)AuCl, [(ACC)Au(PTA)] + (PTA = triazaphosphaadamantane), as well as mixed-carbene compounds [(CAAC)Au(ACC)] + . Representative complexes were characterised by X-ray diffraction which confirmed the mononuclear linear structures without close intermolecular contacts or aurophilic interactions. The redox properties of these complexes have been determined. The compounds were tested against a panel of human cancer cell lines including leukemia (HL 60), breast adenocarcinoma cells (MCF-7) and human lung adenocarcinoma epithelial cell lines (A549), which show varying degrees of cisplatin resistance. The pro-ligand iminium salts and the PTA complexes were non-toxic. By contrast, the CAAC complexes show high cytotoxicity, with IC50 values in the sub-micromolar to ∼100 nanomolar range, even against cisplatin-insensitive MCF-7 and A549 cells. Cationic bis-carbene complexes [( Me2 CAAC)2 M] + (6–8, M = Cu, Ag and Au) proved particularly effective. The mechanism of cell growth control by these complexes remains to be established, although possible modes of action such as inhibition of thioredoxin reductase (TrxR), which is a common pathway for gold NHC compounds, or the formation of reactive oxygen species (ROS) through redox processes, could be ruled out as primary pathways.